The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1128/jvi.03415-12
|View full text |Cite
|
Sign up to set email alerts
|

Echovirus 1 Entry into Polarized Caco-2 Cells Depends on Dynamin, Cholesterol, and Cellular Factors Associated with Macropinocytosis

Abstract: c Enteroviruses invade their hosts by crossing the intestinal epithelium. We have examined the mechanism by which echovirus 1 (EV1) enters polarized intestinal epithelial cells (Caco-2). Virus binds to VLA-2 on the apical cell surface and moves rapidly to early endosomes. Using inhibitory drugs, dominant negative mutants, and small interfering RNAs (siRNAs) to block specific endocytic pathways, we found that virus entry requires dynamin GTPase and membrane cholesterol but is independent of both clathrin-and ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 38 publications
1
42
0
Order By: Relevance
“…Dynamin is a 100-kDa GTPase that plays an essential role in cellular membrane fission during vesicle formation and therefore is required for clathrinand caveola-mediated endocytosis (33,(39)(40)(41)(42). Dynamin has been shown to be required for the internalization of numerous viruses (43)(44)(45)(46). Here we used dynasore, a cell-permeable, noncompetitive dynamin GTPase activity inhibitor (47), to analyze its role in CSFV entry.…”
Section: Resultsmentioning
confidence: 99%
“…Dynamin is a 100-kDa GTPase that plays an essential role in cellular membrane fission during vesicle formation and therefore is required for clathrinand caveola-mediated endocytosis (33,(39)(40)(41)(42). Dynamin has been shown to be required for the internalization of numerous viruses (43)(44)(45)(46). Here we used dynasore, a cell-permeable, noncompetitive dynamin GTPase activity inhibitor (47), to analyze its role in CSFV entry.…”
Section: Resultsmentioning
confidence: 99%
“…Although we had excluded clathrin-and caveolin-mediated endocytosis, we still tested the role of dynamin since it contributes to some forms of macropinocytosis, to fusion pore expansion, and to remodeling of the cytoskeleton (66,75,98). The dynamin inhibitor dynasore reduced HSV-1 gene expression in the four cell lines, again with the weakest effect on Vero cells.…”
Section: Discussionmentioning
confidence: 99%
“…In most cells, macropinocytosis is not constitutively active but needs to be activated (53). A series of classical studies on other viruses, including the poxvirus vaccinia virus (VACV), respiratory syncytial virus, influenza A virus, echovirus 1 (58), and African swine fever virus, revealed that the pathogens are able to activate the pathway (42,(58)(59)(60)(61). As a consequence, virus attachment to the plasma membrane induces membrane "blebbing," triggers actin depolymerization, and increases bulk fluid uptake.…”
Section: Dystroglycan-mediated Lasv Entry Involves An Unusual Pathwaymentioning
confidence: 99%